Editorial: Family culture - Anna Błasiak; Tadeusz Borkowski; Irmina Rostek (Jesuit University Ignatianum in Krakow, 2019)
A new volume - number 48 - of the "Horizons of Education" entitled "Family culture" closes the cycle of scientific studies devoted to "About the family," which illustrated the past and the present of the Polish family in diverse contexts. The Authors reflected on the condition of the contemporary family in the dynamically changing global world, which - according to a large group of researchers - is characterized by a state of permanent anomie, affecting all spheres of human life, including the family. Thanks to the historical analyses presented at the beginning of the cycle, the path the family has travelled from its very beginning to the present day has been reconstructed. We have also shown how the family has been adapting to the world and - inevitably - distancing from its earlier patterns. This adaptation often makes it difficult for us to recognize the contemporary family as the family in its traditional understanding. Today the term "family" embraces much more than it did during the previous centuries...